Laser Monitors for High Speed Imaging of Plasma, Beam and Discharge Processes - Trigub M. V. Maksim Viktorovich; Torgaev S. N. Stanislav Nikolaevich; Evtushenko G. S. Gennady Sergeevich; Drobchik V. V. Vitaliy (Measurement, 2016)
Title screen